2004
DOI: 10.1073/pnas.0307615100
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of phytochrome chromophore-deficient Arabidopsis by expression of phycocyanobilin:ferredoxin oxidoreductase

Abstract: The covalently bound phytochromobilin (P⌽B) prosthetic group is required for the diverse photoregulatory activities of all members of the phytochrome family in vascular plants, whereas by contrast, green algal and cyanobacterial phytochromes use the more reduced linear tetrapyrrole pigment phycocyanobilin (PCB). To assess the functional consequence of the substitution of P⌽B with PCB in plants, the phytochrome chromophore-deficient hy2 mutant of Arabidopsis was transformed with a constitutively expressed pcyA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…Because of the very high expression levels of HY2 expected when driven by the cpcBA promoter, and the structural similarity of the resulting P⌽B chromophore to the native PCB chromophore, it seemed possible that the large proportion of the PBPs in these cells might carry P⌽B and not PCB chromophores. Previously, it was demonstrated that pcyA can largely complement a HY2-deficient strain of A. thaliana; this indicates that the two chromophores are nearly interchangeable in A. thaliana (24). Because this strain carried functional copies of both pcyA and HY2, it was possible that sufficient PCB was available to allow the selective assembly of some PBPs with PCB, as was seen for the strain overexpressing pebA and pebB.…”
Section: Resultsmentioning
confidence: 94%
“…Because of the very high expression levels of HY2 expected when driven by the cpcBA promoter, and the structural similarity of the resulting P⌽B chromophore to the native PCB chromophore, it seemed possible that the large proportion of the PBPs in these cells might carry P⌽B and not PCB chromophores. Previously, it was demonstrated that pcyA can largely complement a HY2-deficient strain of A. thaliana; this indicates that the two chromophores are nearly interchangeable in A. thaliana (24). Because this strain carried functional copies of both pcyA and HY2, it was possible that sufficient PCB was available to allow the selective assembly of some PBPs with PCB, as was seen for the strain overexpressing pebA and pebB.…”
Section: Resultsmentioning
confidence: 94%
“…Fluorescence was detected using FM-BIO II (Hitachi High-Technologies). Absorbance and difference spectra of phytochrome were obtained with a spectrophotometer (HP8453 UV-Visible system, Hewlett Packard GmbH, Waldbronn, Germany) essentially as described previously [18].…”
Section: Phytochrome Detection By Zinc Blot and Difference Spectrummentioning
confidence: 99%
“…Absorption spectra (450-850 nm) were taken in dark then following 60 s R illumination and 60 s FR illumination. For spectrophotometer and filter details, see Kami et al (2004). Difference spectra were obtained by subtraction of R spectra from FR spectra.…”
Section: Pub Synthase Activity Assaymentioning
confidence: 99%